Reflections about an experience related to the academic formation of two behavioral therapists (Brazilian Journal of Behavioral and Cognitive Therapy, 2002)
A supervised program for practical professional training based on the Brazilian literature about the behavioral therapy training was developed for the 5th year of the course of Psychology in a public University and it was applied to two trainees. These two students presented differences between themselves from the beginning to the end of the training, which led to differences in the developed teaching procedure for each trainee. This experience acquired in the supervised practical training led to this present reflection on the variables related to the trainee (theoretical knowledge on the subject, mastering techniques, personal characteristics, motivation), to the supervisor (type of model, way of listening, way of helping, way of providing feedback) and to the supervising (didactics, therapeutics), which are topics mentioned in the literature about how should be the therapist, the supervisor and the act of supervising. The description of a professional practice such as the one developed here in the area of Behavioral Psychological clinician formation may raise some questions not yet answered in the literature but which point to the need of various researches on the subject.